PERAN KEPALA SEKOLAH DALAM MENGEMBANGKAN PROFESIONALITAS GURU DI SMP PLUS AL-MASHDUQIAH KRAKSAN PROBOLINGGO - Faishol Ahmad; Muhammad Ubaidillah (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
In accordance with the vision and mission that has been set. The aims of this study were 1) to know the role of the principal in developing teacher professionalism at SMP Plus Al-Mashduqiah Kraksan Probolinggo. 2) Knowing the principal's efforts in developing teacher professionalism at SMP Plus Al-Mashduqiah Kraksan Probolinggo. 3) Knowing the obstacles of the principal in developing teacher professionalism at SMP Plus Al-Mashduqiah Kraksan Probolinggo. This study uses a descriptive qualitative research approach with data collection methods using interviews, documentation and observation. The results of this study are 1) Implementation of the Management of the Nurul Mustofa Islamic Boarding School in Kutai Regency. The role of the principal in SMP Plus Al-Mashduqiah Kraksan Probolinggo Regency is that the principal acts as a leader, as a manager, as a supervisor, and the principal acts as a motivator. 2) The efforts of the school principal in developing teacher professionalism at SMP Plus Al-Mashduqiah Kraksan Probolinggo Regency, namely by involving teachers in the MGMP (Subject Teacher Consultation), workshops, training (training), as well as providing rewards and punishment. 3) Obstacles to school principals in developing teacher professionalism at SMP Plus Al-Mashduqiah Kraksan Probolinggo Regency include 1) facilities that are less supportive for teachers, 2) lack of community participation for school progress, 3) lack of learning resources for students making it difficult to students understand the lessons conveyed.